Novel euthanasia technique for zebrafish using electric shock in standard group housing aquaria - Ulla Saarinen; Erika Sundell; Lynne Sneddon; Albin Gräns (Scientific Reports)
Abstract Zebrafish are widely used in research, accounting for approximately 50% of all laboratory fish across Europe. Due to their rapid reproduction and aging, effective and practical euthanasia methods are necessary for managing large stocks. This study investigated whether adult zebrafish can be euthanised by delivering an electrical current directly via the water in their housing aquaria. For this, portable plate electrodes were developed for 3.5 and 8.0 L Tecniplast™ housing aquaria. Our results show that adult zebrafish can be euthanised in groups (5 fish per litre) with electrical fields and current densities of at least 6 or 7 VRMS cm−1, and 0.7 or 0.8 ARMS dm−2 in 3.5–8 L aquaria, respectively, when delivered for 30 s in water at 28 °C with a conductivity of 800 µS cm−1 at 50 Hz. If widely implemented, this technique could improve the welfare of the vast number of zebrafish used across the world.